Access and inclusion experiences of LGBTQIA+ students at a South African university - Matsoso, B.; Nendauni, L. (South African Journal of Higher Education, 2026)
This article investigated the experiences of access and inclusion for LGBTQIA+ students at a university in South Africa. From the perspectives of gender identity and social justice, it is evident that the LGBTQIA+ community frequently encounters discrimination and marginalisation. The study employed a qualitative phenomenological approach, utilising semi-structured interviews to collect data from 10 LGBTQIA+ students at a selected South African university. The data was recorded, transcribed, and analysed thematically. The findings reveal that LGBTQIA+ students face substantial challenges, including non-inclusive policies, peer bullying, insufficient faculty awareness, and limited integration and support. Despite constitutional protections, these students continue to experience stigma and barriers within higher education. The study recommends the establishment of a specialised office dedicated to sexual orientation support and the integration of gender and sexual diversity into university curricula to ensure equitable access and opportunities for all students.